Pengaruh E-Procurement dan Akuntabilitas Terhadap Efesiensi Pengadaan Barang/Jasa Pada Dinas Pendidikan Kabupaten Majalengka - Riyadi, Wulan; Hasanah, Nadia (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
Efficiency of Procurement of Goods/Services is the input and output of goods/services produced with scarce input and output in work units or the determination of how to do something that does not waste time, energy and costs. The Education Office of Majalengka Regency in accordance with the circular from the regional leader, implements an online-based procurement process of goods/services in order to streamline the procurement of goods/services, and improve the government management system. The research method used in this study is a quantitative method with a descriptive and verification analysis approach. The population in this study is the Education Office Staff. The sample in this study is the Procurement Staff of Goods/Services at the Education Office of Majalengka Regency. The method used in this study is descriptive and verification analysis carried out with the help of computer software, namely Spss version 29. The results of this study partially show that E- Procurement has an effect on the Efficiency of Procurement of Goods/Services, and Accountability has an effect on the Efficiency of Procurement of Goods/Services. Simultaneously shows that E- Procurement and Accountability have an effect on the Efficiency of Procurement of Goods/Services